Lamb wave mode spectroscopy on complex structures with amplitude-based feature detection. (September 2022) - Purcell, Frederick A.F.; Pearson, Matthew R.; Eaton, Mark J.; Pullin, Rhys
Abstract: The need for fast and effective Non-Destructive Testing (NDT) techniques is ever present. Existing techniques such as ultrasonic testing, whilst established and reliable, face many limitations when considering large structures such as those found in the aerospace and green energy sectors. Wave mode, as well as other wavenumber based filtering techniques have been presented to address many of these limitations. This work describes a novel application of Wave Mode Spectroscopy (WMS) along with feature detection for complex geometric shapes. The specimen's geometry is found during the wavefields measurement through the use of a 3D Scanning Laser Doppler Vibrometer (SLDV) allowing the wavefield to be mapped to a 2D plane with limited distortion of the wavelength and without any prior knowledge of the part's geometry. This was shown to allow WMS to be applied to continuous, multi-frequency wavefields and generate accurate thickness maps. Monogenic signal analysis has been applied to the same measurement data to generate amplitude maps that allow the automatic detection of edge features through the use of a Canny edge detection algorithm.